ANALISIS STRATEGI CUSTOMER RELATIONSHIP MANAGEMENT DALAM MEMBANGUN LOYALITAS PELANGGAN PADA BISNIS DEARLY CAKE - Ayu Wulandari; Vembri Aulia Rahmi (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the implementation of Customer Relationship Management (CRM) strategies in building customer loyalty at Dearly Cake. CRM is an essential approach to enhancing customer relationships, maintaining satisfaction, and creating sustainable loyalty. This study uses a qualitative method with a purposive sampling technique to dig deeper into the CRM strategy implemented by Dearly Cake, the factors that influence its effectiveness, and the challenges faced in the implementation process. The results show that Dearly Cake successfully builds customer loyalty through effective communication, personalized service, and consistent product quality. However, challenges such as limited human resources and suboptimal customer data management hinder the maximum implementation of CRM. The study provides recommendations to enhance technology usage in customer data management and ongoing staff training to support more effective CRM implementation. It is expected that this study will provide insights for other businesses aiming to improve customer loyalty through effective CRM strategies.